Kenyan milk consumers’ behaviour and perceptions of aflatoxin - Walke, M.; Mtimet, Nadhem; Baker, Derek; Waithanji, Elizabeth M.; Lindahl, Johanna F.; Hartmann, M.; Grace, Delia (2014)
Aflatoxin contamination in food is a human health threat in many developing countries. This study examines Kenyan milk consumers’ behaviour related to, and perception of, aflatoxin contamination. The study considered two groups of respondents: raw milk consumers mainly located in peri-urban areas of Nairobi, and processed milk consumers located in urban areas. Results indicate that practically all raw milk consumers and the majority of processed milk consumers boil the milk before its consumption believing that the product is completely safe after boiling. Aflatoxin awareness is very high for the urban milk consumers and relatively high for the peri-urban ones. In both groups, almost half of the respondents who had heard about aflatoxin believe, or know, that it can be transferred into milk. Most respondents, however, did not know how to avoid aflatoxin-contaminated milk. Given the credence characteristic of aflatoxin consumer education and awareness raising programs alone will not be able to solve the problem. Efforts along the whole value chain and at the level of government are needed to reduce the use of aflatoxin spoiled feed and secure aflatoxin safe milk at the consumer level.